Piezoelectrically active acoustic waves confined in a quantum well and their amplification by electron drift - Demidenko, A.A.; Kochelap, V.A.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
In [1] we have studied how the drift of two-dimensional electrons amplifies the acoustic waves confined in quantum wells. The electron-phonon interaction was considered to be due to deformation potential. Here we generalize the theory for the case of piezoelectric electron-phonon interaction. For transverse piezoelectrically active waves in sphalerite-type crystals we obtained solution in the form of localized waves and determined the amplification factor a under the drift of two-dimensional electrons. At frequencies of the order of tens GHz and drift fields of several V/cm a is about tens of cm⁻¹.